Novos corantes derivados de vinil-calcogenil fenotiazinas: síntese e estudo das propriedades fotofísicas e eletroquímicas - Dilelio, Marina Cardoso (2022)
This work presents the synthesis and studies of photophysical and electrochemical behaviour of new phenothiazines derivatives containing the vinyl-chalcogenyl group in different positions of the heterocyclic. This research starts from the assumption that the sulphur atom behaves as a bridge between conjugated structures and can be used on the synthesis of highly conjugated dyes. Its oxidation can lead to compounds with more interesting properties due to the insertion of strong electron-withdrawing groups. Phenothiazine is also an important core on material chemistry because it presents interesting photophysical and optical properties, which can be tuned by modification in its structure. Therefore, the objective of this work was to analyse the effect of the structure modification on the photophysical and electrochemical properties by adding the groups vinyl-chalcogenyl in different positions of phenothiazine. The compounds studied in this work were synthesized via Wittig-Horner reaction and were obtained with high yields (67 to 94%), short reaction times, maximum of 3.5 h, and with good stereoselectivity for the non-oxidate compounds. The sulfoxide was obtained in a mixture of E:Z of 17:1 and just isomer E was obtained on the synthesis of sulfones. Through this studies, it was found that the resonance effects at position 10 of phenothiazine are impaired due to the intra conformation that the structure acquires, resulting from the steric hindrance effect between the tricyclic ring and the ring at position 10. Thus, these derivatives have quantum yields of fluorescence relatively lower (from 0.03 to 0.12) compared to 3-substituted phenothiazines (from 0.13 to 0.90), despite having higher Stokes Shift. The change in the size of the alkyl chain at position 10 did not result in significantly differences in the properties of the compounds. However, the exchange of sulphur atom for selenium resulted in a decrease in fluorescence, a fact caused by the effect of the heavy atom. Advancing with the studies, the increase in the conjugated system when adding two phenothiazines or two vinylic moieties caused a bathochromic effect on the absorption of the compounds, of around 20 nm, but did not increase the fluorescence quantum yield. The oxidation of sulphur to sulfoxide and sulfone resulted in red shifted emission spectra due to the more pronounced electron-withdrawing effect of these groups. On the other hand, the quantum yield and the Stokes shift were similar between the compounds, indicating that simple structures also have interesting properties. Electrochemical studies have shown that the compounds have relatively low oxidation and reduction potentials, which are dependent on the electron-withdrawing fraction. In this way, they present an amphoteric character, important for later application of these compounds in LEDs, organic photovoltaics and in catalysis.